GWAS for CSF TREM2 levels identify new variants implicated on TREM2 biology and Alzheimer disease. (20th December 2022) - Mafimoghaddam, Samira; Wang, Lihua; Gorijala, Priyanka; Timsina, Jigyasha; Nykanen, Niko; Wang, Fengxian; Marquié, Marta; Boada, Mercè; Alvarez, Ignacio; Aguilar, Miquel; Pastor, Pau; Ruiz, Agustín; et al.
Abstract: Background: It is demonstrated that the soluble TREM2 in the cerebrospinal fluid (CSF) is associated with Alzheimer disease (AD). Recent studies by our group found that it is the MS4A4A and/or MS4A6A locus that plays a role in modulating sTREM2 and is also associated with AD risk. The goal of this study is to validate and extend findings from previous studies using a larger cohort, identify functional genes, and determine the overlap of the genetic architecture of CSF TREM2 levels with other traits. Method: We used 3, 033 individuals from Knight ADRC, ADNI, DIAN, and PPMI, and 8, 499, 039 variants (MAF >0.01) to identify protein quantitative trait loci (pQTLs) that modify TREM2 levels via a linear regression including age, sex, first 10 genetic principal components and array/cohort as covariates. TREM2 protein measurements were obtained from SomaScan 7k platform. Colocalization analyses were conducted for AD risk as well as functional genes from eQTLGen. LDSC and GNOVA and Mendelian randomization (MR) is being used to determine the overlap of the genetic architecture of sTREM2 levels with those for AD risk, onset and progression, as well as cardiovascular and lipid traits. Result: The pQTL analysis identified the previously discovered MS4A gene region on chr11 (rs72918674, P = 7.009e‐58) as well as a peak on chr3 (rs73823326, P = 2.227e‐09). The lead variant resides in the intron of MS4A6A gene. Conditional analysis on this variant revealed rs10897026 as an additional independent signal located in the intron of MS4A4A . Chr11 peak colocalized with AD risk (PP‐H4 = 0.97) and MS4AE and MS4A6A expression QTL in blood (PP‐H4 = 0.97 and 0.96, respectively). Four regulatory region variants are in high linkage disequilibrium (LD) with chr3 index variant. RBMS3 and TGFBR2 are two genes flanking the chr3 peak, both expressed in microglia. Conclusion: This is the largest study to date aiming at identifying genetic modifiers of CSF sTREM2. The findings validated discoveries from previous studies and identified a novel signal on chr3 at genome‐wide significance. We propose two new genes, RBMS3 and TGFBR2 on chr3, could be involved in TREM2 biology. Our findings provide new insight to unravel sTREM2 modulators and their role in AD.